1968
DOI: 10.1203/00006450-196807000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Birth Condition and Neuro-Behavioral Organization in the Neonate

Abstract: The neuro-behavioral organization of three groups of infants who differed in their condition at birth as determined by their Apgar score was examined during the first week of life. At the time of testing, all infants, regardless of birth status, were in good condition according to clinical evaluation. Testing consisted of the presentation of 30 lateralized somesthetic stimuli to the perioral region of each infant (15 to each side). The response measure used was the lateral direction of the first head turn. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1977
1977
1995
1995

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…However, as is always the case when a difference between premature and full-term infants is observed, the difference may stem not from the absence of intrauterine experience but rather from the same cituses and physiological consequences as contributed to the prematurity itself. This possibility receives some support from the previous finding that babies born in poor condition as evidenced by low Apgar scores exhibit a weaker lateral difference in response to somesthetic stimulation than do infants born in good condition (Turkewitz, Moreau, & Birch, 1968).…”
Section: Discussionmentioning
confidence: 84%
“…However, as is always the case when a difference between premature and full-term infants is observed, the difference may stem not from the absence of intrauterine experience but rather from the same cituses and physiological consequences as contributed to the prematurity itself. This possibility receives some support from the previous finding that babies born in poor condition as evidenced by low Apgar scores exhibit a weaker lateral difference in response to somesthetic stimulation than do infants born in good condition (Turkewitz, Moreau, & Birch, 1968).…”
Section: Discussionmentioning
confidence: 84%
“…In view of these apparent differences between full-term and premature infants, a direct comparison was made between the data obtained in the present study and those previously obtained from comparable testing of a group of 71 full-term infants ("high Apgar group" from Turkewitz et al, 1968). Infants who were 36 weeks and older gave the strongest indication of being more likely to make ipsilateral than contralateral responses; therefore all comparisons with the full-term infants were based on tests conducted when the premature infants were at these older ages.…”
Section: Comparison With Full-term Infantsmentioning
confidence: 95%
“…Prior investigations have indicated that full-term infants: (1) make head-turning responses to somesthetic stimulation of the perioral region (Prechtl, 1958;Turkewitz P t al., 1965); (2) make nearly all responses toward the stimulus (Prechtl, 1958;Turkewitr et al, 1965); (3) exhibit a marked lateral difference in their ipsilateral responding such that they make more ipsilateral turns to stimulation of the right than of the left (Turkewitz et al, 1965); and (4) make more contralateral responses to stimulation of the left than to stimulation of the right (Turkewitz et al, 1967;Turkewitz, Moreau, & Birch, 1968). The current data indicate that premature infants are similar to full-term infants in that they are responsive to somesthetic stimulation, tend to make more ipsilateral responses, and tend to make more contralateral responses to stimulation of the left than of the right.…”
Section: Comparison With Full-term Infantsmentioning
confidence: 99%
“…Because birth condition has been shown to disrupt asymmetries (Turkewitz, Moreau, Birch, 1968), an ontogenetic interpretation of development of the lateral asymmetries from the 2 studies cited above is unclear. Specifically, preterm lateral head turning response may not be a later developing behavior but may have been affected by illness rather than by prematurity alone.…”
mentioning
confidence: 99%